2009
DOI: 10.1002/adma.200802783
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis and Shape Evolution of Single‐Crystal Cuprous Oxide

Abstract: Various morphologies of single‐crystal Cu2O such as cube, octahedron, {110} truncated octahedron, and microrhombic dodecahedron with {110} surfaces are prepared in high yield through a facile solution‐based one‐step reduction method in an alkaline H2O/ethanol/oleic acid system in the presence of d‐(+)‐glucose. The formation mechanism of these microcrystals has been clarified as the synergic effect of oriented attachment and ripening mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
179
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(187 citation statements)
references
References 30 publications
8
179
0
Order By: Relevance
“…On the basis of our experimental data, a mechanism of Cu 2 O particle formation was hypothesized that is consistent with earlier reports [14,16,[41][42][43][44][45][46][47][48][49][50]. Addition of NH 2 OHÁHCl into the reaction system results in heterogeneous nucleation [51], yielding primary Cu 2 O nanoparticles due to the reduction of Cu(OH) 2 .…”
Section: Mechanism Of Formationsupporting
confidence: 77%
“…On the basis of our experimental data, a mechanism of Cu 2 O particle formation was hypothesized that is consistent with earlier reports [14,16,[41][42][43][44][45][46][47][48][49][50]. Addition of NH 2 OHÁHCl into the reaction system results in heterogeneous nucleation [51], yielding primary Cu 2 O nanoparticles due to the reduction of Cu(OH) 2 .…”
Section: Mechanism Of Formationsupporting
confidence: 77%
“…Meanwhile, C18N3 play its role in the ripening process as a face-selective adsorption additive to control the final shape of the microcrystals to control the final shape of the microcrystals. Therefore, Cu(OH) 2 nano/microcrystals are obtained through the synergic effects of oriented attachment and a ripening mechanism, which has been reported by Gao et al , who successfully prepared a series of Cu 2 O single crystals by using a facile solution-phase route [30]. To demonstrate this kind of crystal growth, a control experiment was conducted in which seed crystals were produced and grown without C18N3.…”
Section: Resultsmentioning
confidence: 93%
“…[32][33][34] Different morphologies of the samples with different concentrations of the surfactant were also reported by Liang and co-workers. [35] They demonstrated that oleic acid could selectively adsorb onto {100}, {111}, and {110} surfaces with increasing concentration, thereby resulting in different growth rates along different surfaces, and therefore microcubes, microoctahedra, truncated octahedra, and microrhombic dodecahedra of Cu 2 O were formed. According to the above experimental results and analysis, the formation of different shapes of PbS is ascribed to the strong interaction between the surface of PbS particles and citric acid molecules.…”
Section: Investigation Of Influencing Factorsmentioning
confidence: 98%